EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI TERHADAP KEMANDIRIAN BELAJAR SISWA DI RUMAH - Irfan Sugianto; Savitri Suryandari; Larasati Diyas Age (Jurnal Inovasi Penelitian, 2020)
The goal of learning independence is the curiosity of each student to find new things, which will encourage students to continue to look for problem solving so that in this case the independence of student learning is inseparable from the effectiveness of the learning model applied by the teacher. This research uses library research methods and the type of data used is secondary data. The literature review and from previous research data it can be concluded that inquiry learning towards student learning independence can be applied at school.